2021
DOI: 10.1186/s12302-021-00548-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term associations of air pollution and meteorological variables on the incidence and severity of COVID-19 in Madrid (Spain): a time series study

Abstract: Background There are studies that analyze the role of meteorological variables on the incidence and severity of COVID-19, and others that explore the role played by air pollutants, but currently there are very few studies that analyze the impact of both effects together. This is the aim of the current study. We analyzed data corresponding to the period from February 1 to May 31, 2020 for the City of Madrid. As meteorological variables, maximum daily temperature (Tmax) in ºC and mean daily absol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
(58 reference statements)
0
7
0
Order By: Relevance
“…This pollutant can also react with volatile organic compounds and the sun's ultraviolet rays to produce tropospheric ozone, which poses a serious health threat such as inducing airways inflammation and increasing airway hyperreactivity [ 15 17 ]. In previous studies, it was shown that particulate pollutants, e.g., PM 2.5 , PM 10 , NO 2 and ozone were the most important pollutants contributing to COVID-19 mortality and incidence [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This pollutant can also react with volatile organic compounds and the sun's ultraviolet rays to produce tropospheric ozone, which poses a serious health threat such as inducing airways inflammation and increasing airway hyperreactivity [ 15 17 ]. In previous studies, it was shown that particulate pollutants, e.g., PM 2.5 , PM 10 , NO 2 and ozone were the most important pollutants contributing to COVID-19 mortality and incidence [ 18 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to air pollutants was positively associated with incidence ( Stieb et al, 2020 ), mortality ( Wu et al, 2020 ), and case fatality rate ( Tian et al, 2021 ) of COVID-19. Linares et al (2021) indicated that NO 2 exposure was more prominent to be associated with higher severity of COVID-19 compared with other pollutants. Increasing evidence has sought the potential mechanism of air pollutants and adverse outcomes of COVID-19.…”
Section: Discussionmentioning
confidence: 97%
“… Linares et al (2021) analyzed the association between daily temperature and absolute humidity with the daily incidence, hospital and intensive care unit admissions, and death rates in the period from February 01 to May 31, 2020, for the City of Madrid ( Linares et al, 2021 ). The authors showed that temperature and absolute humidity are negatively associated with all of the dependent variables considered, except in the case of deaths.…”
Section: Discussionmentioning
confidence: 99%